Induction of Tetraploids from Petiole Explants through Colchicine Treatments in Echinacea purpurea L. (19th August 2009) - Nilanthi, Dahanayake; Chen, Xiao-Lu; Zhao, Fu-Cheng; Yang, Yue-Sheng; Wu, Hong
Abstract : Petiole explants were obtained from in vitro grown diploid (2 x = 22 ) Echinacea purpurea plantlets. Shoots were regenerated by culturing the explants on MS basal medium containing 0.3 mg/L benzyladenine (BA), 0.01 mg/L naphthaleneacetic acid (NAA) and four concentrations (30, 60, 120, and 240 mg/L) of colchicine for 30 days, or 120 mg/L of colchicine for various durations (7, 14, 21, and 28 days). The regenerated shoots were induced to root on MS basal medium with 0.01 mg/L NAA, and then the root-tips of the regenerated shoots were sampled for count of chromosome number. It was found that a treatment duration of >7 days was necessary for induction of tetraploid (4 x = 44 ) shoots, and treatment with 120 mg/L colchicine for 28 days was the most efficient for induction of tetraploids, yielding 23.5% of tetraploids among all the regenerated shoots. Chimeras were observed in almost all the treatments. However, the ratio of tetraploid to diploid cells in a chimeric plant was usually low. In comparison with diploid plants, tetraploid plants in vitro had larger stomata and thicker roots with more root branches, and had prominently shorter inflorescence stalk when mature.